Freestanding film, electrode for secondary battery, secondary battery including same, and method for manufacturing electrode

A dry method using a free-standing film with directional patterns on the electrode layer addresses the issue of high-temperature damage in wet manufacturing, enhancing peel and adhesive strength while reducing binder reliance.

JP7600378B2Active Publication Date: 2024-12-16LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023514135
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-06
Filing Date
2022-01-10
Publication Date
2024-12-16
Estimated Expiration
2042-01-10

AI Technical Summary

Technical Problem

Existing secondary battery electrodes are manufactured using wet methods that require high-temperature heat treatment, which can damage metal oxides, and there is a need for a dry method to improve peel strength and adhesive strength.

Method used

A free-standing film with a directional concavo-convex pattern is used to form an electrode layer, which includes an active material, conductive agent, and binder, attached to an electrode current collector through a dry process, utilizing a two-roll mill to create patterns with specific intervals and depths.

Benefits of technology

The method enhances peel strength and adhesive strength of the electrode, minimizing binder use while maintaining structural integrity, and improving the manufacturing process efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600378000002
    Figure 0007600378000002
  • Figure 0007600378000003
    Figure 0007600378000003
  • Figure 0007600378000004
    Figure 0007600378000004
Patent Text Reader

Abstract

A freestanding film according to one embodiment of the present invention includes a directional pattern on at least one surface.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0004143 filed on January 12, 2021, and Korean Patent Application No. 10-2022-0002294 filed on January 6, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a freestanding film, an electrode for a secondary battery, a secondary battery including the same, and a method for manufacturing the electrode, and more specifically, to a freestanding film having improved peel strength and adhesive strength, an electrode for a secondary battery, a secondary battery including the same, and a method for manufacturing the electrode. [Background technology]

[0003] Demand for secondary batteries as an energy source is rapidly increasing along with technological development and increasing demand for mobile devices. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] In particular, secondary batteries have attracted much attention as energy sources not only for mobile devices such as mobile phones, digital cameras, laptops, and wearable devices, but also for power plants such as electric bicycles, electric cars, and hybrid electric cars.

[0005] In addition, as interest in environmental issues grows, much research is being conducted on electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline and diesel vehicles, which are one of the main causes of air pollution. Nickel-metal hydride secondary batteries are mainly used as the power source for such electric vehicles and hybrid electric vehicles, but research into using lithium secondary batteries with high energy density and discharge voltage is being actively conducted, and some of them are already at the commercialization stage.

[0006] Existing secondary battery electrodes have generally been manufactured using a wet process. However, when manufacturing electrodes using a wet process, a heat treatment process at high temperatures is required, which may damage the metal oxide. This has led to an increased need for the development of electrodes manufactured using a dry process. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a free-standing film having improved peel strength and adhesive strength, an electrode for a secondary battery, a secondary battery including the same, and a method for manufacturing the electrode.

[0008] The problems to be solved by the present invention are not limited to the problems described above, and problems not mentioned will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from this specification and the accompanying drawings. [Means for solving the problem]

[0009] A freestanding film according to one embodiment of the present invention includes a directional pattern on at least one surface.

[0010] The pattern may be a concave-convex pattern.

[0011] The patterns may have spacings of 100 μm to 2000 μm.

[0012] The pattern may have a depth of 1.5 μm to 35 μm.

[0013] According to another embodiment of the present invention, there is provided an electrode for a secondary battery, comprising: an electrode current collector; and an electrode layer disposed on the electrode current collector. The electrode layer comprises an electrode composition in which an active material, a conductive agent, and a binder are dry-mixed; the electrode composition is formed into a free-standing film; and the free-standing film comprises a directional pattern on at least one surface.

[0014] The pattern may be a concave-convex pattern.

[0015] The patterns may have spacings of 100 μm to 2000 μm.

[0016] The pattern may have a depth of 1.5 μm to 35 μm.

[0017] The free-standing film may be attached onto the electrode current collector such that the surface on which the pattern is formed is in contact with the electrode current collector.

[0018] The active material may include at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with a spinel structure, LiMn2O4 in which a portion of Li is substituted with an alkaline earth metal ion, a disulfide compound, Fe2(MoO4)3, and lithium manganese oxide (LMO, lithium manganese oxide).

[0019] The binder can include polytetrafluoroethylene (PTFE).

[0020] The freestanding film may have a peel strength of 10 gf / 20 mm or more and 15 gf / 20 mm or less.

[0021] According to yet another embodiment of the present invention, a method for manufacturing an electrode for a secondary battery includes dry-mixing an active material, a conductive agent, and a binder to prepare a mixture, applying a shear force to the mixture to prepare a free-standing film, forming a directional pattern at regular intervals on the free-standing film, and attaching the free-standing film onto an electrode collector to form an electrode for a secondary battery.

[0022] The pattern may be a concave-convex pattern.

[0023] The patterns may have spacings of 100 μm to 2000 μm.

[0024] The pattern may have a depth of 1.5 μm to 35 μm.

[0025] The free-standing film may be attached onto the electrode current collector such that the surface on which the pattern is formed is in contact with the electrode current collector.

[0026] The step of forming the pattern may include one of forming the pattern on the freestanding film by an embossed pattern formed on a roll that winds the freestanding film, adjusting the speed of the roll, and setting different gear ratios of a two roll mill.

[0027] The step of setting different gear ratios of the two roll mills may include setting the gear ratios differently to generate backlash.

[0028] The binder can include polytetrafluoroethylene (PTFE).

[0029] A secondary battery according to yet another embodiment of the present invention includes the above-mentioned free-standing film. Effect of the Invention

[0030] According to an embodiment of the present invention, a secondary battery electrode is manufactured by a dry process including a step of forming a pattern on a free-standing film, thereby improving peel strength and adhesive strength.

[0031] The effects of the present invention are not limited to the effects described above, and effects not mentioned will be clearly understood by those having ordinary skill in the art to which the present invention pertains from this specification and the accompanying drawings. [Brief description of the drawings]

[0032] [Figure 1] FIG. 2 is a schematic diagram illustrating a pattern of a free-standing film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a pattern of a free-standing film according to one embodiment of the present invention. [Diagram 3] 4 is a flowchart illustrating a method for manufacturing an electrode for a secondary battery according to another embodiment of the present invention. [Figure 4] 1 is a graph comparing peel strengths according to patterns formed on a free-standing film included in an electrode for a secondary battery in Examples and Comparative Examples of the present invention. [Diagram 5] 1 is a graph comparing peel strength according to an interval of a pattern formed on a free-standing film included in an electrode for a secondary battery in Examples and Comparative Examples of the present invention. [Figure 6] 1 is a graph comparing peel strength according to depth of a pattern formed on a free-standing film included in an electrode for a secondary battery in Examples and Comparative Examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;

[0034] Hereinafter, an electrode for a secondary battery according to one embodiment of the present invention will be described.

[0035] According to an embodiment of the present invention, an electrode for a secondary battery includes an electrode current collector and an electrode layer formed as a freestanding film on the electrode current collector, the electrode layer including an electrode composition in which an active material, a conductive agent, and a binder are dry-mixed.

[0036] The electrode layer is formed during the process of manufacturing a free-standing film, and the electrode layer may be attached to the electrode collector by a lamination process. Here, the electrode layer may have a pattern having a directionality. The pattern according to the present embodiment may have an interval of about 100 μm to 2000 μm. Also, the pattern according to the present embodiment may have a depth of about 1.5 μm to 35 μm. At this time, the interval of the pattern may be defined as the distance between adjacent grooves, and the depth of the pattern may be defined as the recessed depth of the grooves. The pattern is formed on one surface of the electrode layer attached to the electrode collector.

[0037] As a result, the electrode layer can have high adhesive strength when attached to the electrode collector, and the electrode layer can have a peel strength of 10 gf / 20 mm to 15 gf / 20 mm from the electrode collector. In addition, the pattern can achieve an adhesive strength improvement effect, thereby minimizing the use of existing binders.

[0038] If the spacing between the electrode layer patterns according to the present embodiment is too small, the secondary battery electrode may crack and not maintain a certain level of strength, leading to breakage. Also, if the spacing between the electrode layer patterns is too large, it is essentially the same as if the patterns did not exist, and the effect of improving adhesive strength due to the formation of the patterns may not be obtained or may be reduced.

[0039] In addition, if the depth of the electrode layer pattern is too deep, the secondary battery electrode may crack and break, and if the depth of the electrode layer pattern is too shallow, it is essentially the same as if the pattern did not exist, and the effect of improving adhesion due to the formation of the pattern may not be obtained or may be reduced.

[0040] Hereinafter, each component included in the electrode for a secondary battery according to an embodiment of the present invention will be described in detail.

[0041] Fig. 1 is a schematic diagram showing a pattern formed on a free-standing film of an electrode for a secondary battery according to an embodiment of the present invention, and Fig. 2 is a cross-sectional view of the pattern of the free-standing film.

[0042] 1 and 2, the electrode layer included in the secondary battery electrode according to the present embodiment includes an electrode composition in which an active material, a conductive agent, and a binder are dry-mixed, and the electrode composition is manufactured into a free-standing film. At this time, the free-standing film included in the secondary battery electrode according to the present embodiment includes a directional pattern on at least one surface. In particular, the directional pattern may include a plurality of patterns formed in one direction as shown in FIG. 1, and at this time, the directional pattern may be a concave-convex pattern.

[0043] More specifically, in the electrode layer included in the electrode for a secondary battery according to the present embodiment, the pattern includes a plurality of convex portions 100 and groove portions 200 that are alternately formed and positioned on the freestanding film. Here, the plurality of convex portions 100 may be formed to have a uniform height, and the plurality of groove portions 200 may be formed to have a uniform recessed depth, but are not limited thereto. In this case, the interval between adjacent groove portions 200 may be defined as the interval d1 of the pattern. If the interval d1 of the pattern is out of a certain range, the effect to be achieved through the embodiment of the present invention due to the formation of the pattern may not be achieved or the effect may be reduced.

[0044] At this time, the pattern having directionality may include a direction in which the grooves 200 are formed long (horizontal direction in FIG. 1) and a direction in which the interval d1 of the pattern is formed (vertical direction in FIG. 1). That is, the directionality of the pattern having directionality may refer to a direction in which the grooves 200 are formed long. As described below, the pattern may be formed while a two-roll mill passes a freestanding film, and the direction in which the grooves 200 of the pattern are formed may be formed in a direction perpendicular to the direction in which the freestanding film passes through the two-roll mill. Therefore, the directionality of the pattern having directionality may be a direction perpendicular to the direction in which the freestanding film passes through the two-roll mill. Therefore, the direction in which the interval d1 of the pattern is formed may coincide with the direction in which the freestanding film passes through the two-roll mill.

[0045] The pattern serves to improve the adhesion between the free-standing film and the electrode layer and the electrode current collector.

[0046] The pattern interval d1 may be 100 μm or more and 2000 μm or less. More preferably, the pattern interval d1 may be 150 μm or more and 1900 μm or less. As an example, the pattern interval d1 may be 200 μm or more and 1800 μm or less.

[0047] As a result, in the electrode for a secondary battery according to the present embodiment, the interval d1 of the pattern is within the above-mentioned range, and the pattern can improve the adhesive strength between the freestanding film and the electrode current collector, and the peel strength of the freestanding film can be improved. In addition, by forming the pattern on the freestanding film, the use of a binder can be minimized.

[0048] On the other hand, if the pattern spacing d1 is outside the above range, the adhesive strength improving effect due to the pattern may be reduced, and the peel strength may be reduced. More specifically, if the pattern spacing d1 is less than 100 μm, excessive pattern formation on the freestanding film may cause cracks in the secondary battery electrode, weakening the strength of the electrode. In addition, the weakened strength may increase the possibility of the secondary battery electrode breaking. On the other hand, if the pattern spacing d1 is more than 2000 μm, the adhesive strength improving effect may not be achieved or may be reduced, the same as when the pattern is not formed.

[0049] In addition, the depth H of the pattern can be defined as the recessed depth of the grooves 200 from the protrusions 100 or the protruding height of the protrusions 100 from the grooves 200 .

[0050] In this case, the depth H of the pattern may be 1.5 μm or more and 35 μm or less. More preferably, the depth H of the pattern may be 1.8 μm or more and 32 μm or less. As an example, the depth H of the pattern may be 2 μm or more and 30 μm or less.

[0051] Therefore, in the electrode for a secondary battery according to the present embodiment, the depth H of the pattern is within the above-mentioned range, and the pattern can improve the adhesive strength between the freestanding film and the electrode current collector, and the peel strength of the freestanding film can be improved. In addition, by forming the pattern on the freestanding film, the use of a binder can be minimized.

[0052] On the other hand, if the depth H of the pattern is outside the above range, the adhesive strength improving effect due to the pattern may decrease, and the peel strength may decrease. More specifically, if the depth H of the pattern exceeds 35 μm, excessive pattern formation on the freestanding film may cause cracks in the secondary battery electrode, weakening the strength of the electrode. In addition, the weakened strength may increase the possibility of the secondary battery electrode breaking. On the other hand, if the depth H of the pattern is less than 1.5 μm, the adhesive strength improving effect may not be achieved or may be reduced, the same as when the pattern is not formed.

[0053] In order to form a pattern according to the present embodiment, an embossed pattern is formed on a roll that winds the freestanding film, so that the pattern of the roll is transferred to the surface of the freestanding film. Alternatively, the speed of the roll that winds the freestanding film may be adjusted to form a pattern on the surface of the freestanding film. Alternatively, a two-roll mill (2 roll mill) may pass the freestanding film while having different gear ratios, so that a pattern is formed on the surface of the freestanding film. When the two-roll mill (2 roll mill) is used, backlash may occur due to the difference in the gear ratios, which is set differently. The backlash refers to a gap that occurs when the driving roll rotates but the driven roll stops when the gears are connected to rotate in both directions on one axis of the two-roll mill, and at this time, a shear force is generated to form a pattern on the freestanding film. Also, the interval d1 of the pattern and the depth H of the pattern can be adjusted according to the size of the backlash.

[0054] The active material may be a positive electrode active material. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide, lithium copper oxide (Li2CuO2), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn2O4 in which part of Li in the chemical formula is replaced with an alkaline earth metal ion, disulfide compound, Fe2(MoO4)3, etc.

[0055] For example, the active material may include lithium manganese oxide (LMO). Here, the active material is included in an amount of 85 wt% to 99 wt% based on the total weight of the electrode composition. More preferably, the active material is included in an amount of 87 wt% to 98 wt% based on the total weight of the electrode composition. For example, the active material is included in an amount of 89 wt% to 97 wt% based on the total weight of the electrode composition.

[0056] The binder plays a role of improving the adhesion between active material particles and the adhesive strength between the active material and the current collector. Specific examples include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and these may be used alone or in combination of two or more.

[0057] For example, the binder may include polytetrafluoroethylene (PTFE). Here, the content of the binder may be 1 wt % or more and 5 wt % or less based on the total weight of the electrode composition. More preferably, the content of the binder may be 1.5 wt % or more and 4.5 wt % or less based on the total weight of the electrode composition. For example, the content of the binder may be 2 wt % or more and 4 wt % or less based on the total weight of the electrode composition.

[0058] The conductive agent is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, graphene, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or a mixture of two or more of these can be used. Here, the conductive agent is contained in an amount of 1% by weight to 10% by weight based on the total weight of the electrode. More preferably, the content of the conductive agent may be 1% by weight to 5% by weight based on the total weight of the electrode composition. As an example, the content of the conductive agent may be 2% by weight to 4% by weight based on the total weight of the electrode composition.

[0059] The above-described secondary battery electrode may be included as a positive electrode in a secondary battery according to another embodiment of the present invention. More specifically, the secondary battery according to another embodiment of the present invention may include an electrode assembly including the positive electrode, the negative electrode, and a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0060] The negative electrode, like the secondary battery electrode, is prepared by coating a negative electrode composition containing a negative electrode active material, a polymer material, a conductive agent, etc., on a negative electrode current collector.

[0061] The negative electrode is also manufactured in a form in which a negative electrode composition including a negative electrode active material is attached or coated on a negative electrode current collector, and the negative electrode composition may further include a conductive agent and a polymer material as described above together with the negative electrode active material.

[0062] The negative electrode active material may be a common negative electrode active material for lithium secondary batteries in the art, and examples thereof include lithium metal, lithium alloy, petroleum coke, activated carbon, graphite, silicon, tin, metal oxides, or other carbons.

[0063] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. can be used.

[0064] The separation membrane separates the negative electrode and the positive electrode and provides a path for lithium ion migration. Any membrane that is normally used as a separator in a lithium secondary battery can be used without any particular restriction. In particular, a membrane that has low resistance to the migration of electrolyte ions and is excellent in the ability to moisten the electrolyte is preferred.

[0065] In addition, examples of the electrolyte solution used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0066] Specifically, the electrolyte may contain an organic solvent and a lithium salt. The organic solvent may be any organic solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. The lithium salt may be any lithium salt that can provide lithium ions used in the lithium secondary battery. In addition to the above-mentioned components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives are contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0067] FIG. 3 is a flowchart illustrating a method for manufacturing an electrode for a secondary battery according to another embodiment of the present invention.

[0068] Referring to FIG. 3, the method for manufacturing an electrode according to the present embodiment includes a premixing step S10 of mixing an active material, a conductive agent, and a binder, a high shear mixing step S20 of applying a shear force to the mixture mixed in the premixing step, a step S30 of manufacturing a free-standing film using the high shear mixed mixture, a step S40 of forming a pattern on a surface of the free-standing film, and a step S50 of attaching the patterned free-standing film onto an electrode current collector by a lamination process to manufacture an electrode for a secondary battery.

[0069] Here, the premixing step S10 may dry mix the active material, the conductive agent, and the binder.

[0070] The present invention will be described below with reference to more specific examples. However, the following examples are provided to illustrate the present invention and are not intended to limit the scope of the present invention.

[0071] <Example 1> A premixing step was performed to prepare a mixture by dry mixing the active material, conductive agent, and binder using a Waring blender. Here, the active material was 94 wt% lithium manganese oxide (LMO), the conductive agent was 3 wt% Super C65, and the binder was 3 wt% polytetrafluoroethylene (PTFE). At this time, the premixing step S10 was performed at 5000 rpm for 1 minute to induce only the mixing of the active material, conductive agent, and binder.

[0072] Thereafter, a high shear mixing step S20 was carried out to activate polytetrafluoroethylene (PTFE) by applying shear force to the mixture produced in the premixing step S10 using a Bench Kneader PBV-0.1L device manufactured by Irie Shoji Co., Ltd. The high shear mixing step S20 was carried out for 5 minutes at 30 rpm.

[0073] Thereafter, the electrode composition prepared in the high shear mixing step S20 was molded into a film having a length of 20 mm and a width of 20 mm using a two roll mill MR-3 made by Inoue Seisakusho Co., Ltd., to prepare a freestanding film (S30). The freestanding film had a thickness of 200 μm and a porosity of 30%.

[0074] In this case, the following method was used to form a pattern on the freestanding film. Using the two-roll mill device, the gear ratio of each roll was made different to generate backlash. The backlash refers to a gap that occurs when the driving roll rotates while the subordinate roll stops when the gears are connected to rotate bidirectionally on a single shaft of the two roll crushers, and a pattern can be formed on the freestanding film due to the instantaneous generation of shear force. The size of the backlash was adjusted using the above method to form a pattern with a 200 μm interval and a 10 μm depth.

[0075] <Example 2> In the above-mentioned Example 1, the interval between the patterns was set to 500 μm. Except for this, a free-standing film was produced in the same manner as in the above-mentioned Example 1.

[0076] <Example 3> In the above-mentioned Example 1, the interval between the patterns was set to 1700 μm. Except for this, a free-standing film was produced in the same manner as in Example 1.

[0077] <Example 4> In Example 2, the pattern was formed to have a depth of 2 μm. Except for this, a free-standing film was produced in the same manner as in Example 2.

[0078] <Example 5> In Example 2, the pattern was formed to a depth of 30 μm. Except for this, a free-standing film was produced in the same manner as in Example 2.

[0079] <Comparative Example 1> The pattern was not formed in Example 1. Except for this, a free-standing film was produced in the same manner as in Example 1.

[0080] <Comparative Example 2> In the above-mentioned Example 1, the interval between the patterns was set to 70 μm. Except for this, a free-standing film was produced in the same manner as in the above-mentioned Example 1.

[0081] <Comparative Example 3> In the above-mentioned Example 1, the interval between the patterns was set to 2500 μm. Except for this, a free-standing film was produced in the same manner as in Example 1.

[0082] <Comparative Example 4> In Example 2, the pattern was formed to a depth of 1 μm. Except for this, a free-standing film was produced in the same manner as in Example 2.

[0083] <Comparative Example 5> In Example 2, the pattern was formed to have a depth of 40 μm. Except for this, a free-standing film was produced in the same manner as in Example 2.

[0084] <Experimental Example 1 (Measurement of Peel Strength)> For each of the freestanding films produced in Examples 1 to 5 and Comparative Examples 1 to 5, a double-sided tape was attached to a glass slide, and then the surface of the freestanding film was attached to the surface of the double-sided tape. The glass slide was then fixed in a flat state, and the end portion of the electrode current collector was fixed to a jig, and the electrode current collector was pulled in a direction perpendicular (90 degrees) to the ground on which the glass slide was placed, using an Instron UTM device. The peel strength between the electrode current collector and the freestanding film was measured at a speed of 300 mm / min, and the average value was derived, and the results are shown in Table 1.

[0085] [Table 1]

[0086] <Analysis of Experimental Results 1 - Pattern Spacing> FIG. 4 is a graph comparing peel strengths according to patterns formed on free-standing films of electrodes for secondary batteries according to examples of the present invention and comparative examples.

[0087] FIG. 5 is a graph comparing peel strength according to the spacing of patterns formed on free-standing films of electrodes for secondary batteries according to the examples of the present invention and the comparative examples.

[0088] At this time, it was confirmed that the peel strength gradually decreased in the order of Example 1, Example 2, Example 3, Comparative Example 3, and Comparative Example 1.

[0089] 4, in Comparative Example 2, the electrodes were broken by cracks during the measurement, making it impossible to measure, and it was confirmed that the strength of the electrodes cannot be maintained when the spacing between the patterns of the free-standing film is too narrow. Also, in Comparative Example 3, the spacing between the patterns of the standing film was wide, and it was confirmed that the peel strength was not excellent, being essentially the same as a free-standing film without a pattern. In other words, it was confirmed that the peel strength was not excellent when the spacing between the patterns of the free-standing film was too narrow or wide compared to the Examples.

[0090] This confirmed that when the free-standing film has a pattern interval as in Examples 1 to 3, the peel strength is excellent.

[0091] <Analysis of Experimental Results 2 - Pattern Depth> FIG. 6 is a graph comparing peel strength according to the depth of a pattern formed on a free-standing film of an electrode for a secondary battery according to an embodiment of the present invention and a comparative example.

[0092] At this time, it was confirmed that the peel strength gradually decreased in the order of Example 5, Example 2, Example 4, and Comparative Example 4.

[0093] 5, in Comparative Example 5, the electrode was broken by a crack during the measurement, making it impossible to measure, and it was confirmed that the strength of the electrode cannot be maintained when the pattern depth of the freestanding film is too deep. Also, in Comparative Example 4, the pattern depth of the freestanding film was shallow, and it was confirmed that the peel strength was not excellent because it was essentially the same as a freestanding film without a pattern. In other words, it was confirmed that the peel strength was not excellent when the pattern depth of the freestanding film was too high or too low compared to the Examples.

[0094] As a result, it was confirmed that when the pattern depth of the freestanding film is within the interval ranges disclosed in Examples 2, 4, and 5, the peel strength is excellent.

[0095] In addition, through the examples and comparative examples, it was confirmed that Example 5 had the best peel strength, and therefore, when the pattern spacing and depth are as disclosed in Example 5, a freestanding film with the best peel strength can be produced.

[0096] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention.

Claims

1. An electrode comprising a dry mixed electrode composition comprising an active material, a conductive agent, and a binder, At least one surface includes a directional pattern; The pattern is a concave-convex pattern, The pattern has a spacing of 100 μm to 2000 μm; the pattern has a depth of 1.5 μm to 35 μm; The content of the binder is 2% by weight or more and 4% by weight or less based on the total weight of the dry mixed electrode composition.

2. An electrode current collector; an electrode layer located on the electrode current collector; The electrode layer includes a dry mixed electrode composition of an active material, a conductive agent, and a binder, the dry mixed electrode composition is a free-standing film; The freestanding film includes a directional pattern on at least one surface, The pattern is a concave-convex pattern, The pattern has a spacing of 100 μm to 2000 μm; the pattern has a depth of 1.5 μm to 35 μm; The free-standing film is attached onto the electrode current collector so that the surface on which the pattern is formed is in contact with the electrode current collector.

3. The active material is lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium copper oxide (Li 2 CuO 2 ), vanadium oxide, Ni-site type lithium nickel oxide, lithium manganese composite oxide, lithium manganese composite oxide with spinel structure, LiMn 2 O 4 , disulfide compound, Fe 2 (MoO 4 ) 3 3. The electrode for a secondary battery according to claim 2, comprising at least one of:

4. The electrode for a secondary battery according to claim 2 , wherein the binder comprises polytetrafluoroethylene (PTFE).

5. The electrode for a secondary battery according to claim 2 , wherein the free standing film has a peel strength of 10 gf / 20 mm or more and 15 gf / 20 mm or less.

6. dry mixing an active material, a conductive agent, and a binder to produce a mixture; applying shear force to the mixture to produce a free-standing film; forming a pattern having a directional pattern with a constant interval on the free-standing film; and attaching the free-standing film onto an electrode current collector to form an electrode for a secondary battery; The pattern is a concave-convex pattern, The pattern has a spacing of 100 μm to 2000 μm; the pattern has a depth of 1.5 μm to 35 μm; The method for manufacturing an electrode for a secondary battery, wherein the free-standing film is attached onto the electrode current collector so that the surface on which the pattern is formed is in contact with the electrode current collector.

7. 7. The method of claim 6, wherein the forming of the pattern includes one of forming the pattern on the freestanding film by an embossed pattern formed on a roll that winds the freestanding film, adjusting the speed of a roll that winds the freestanding film, and setting different gear ratios of a two-roll mill.

8. The method of claim 7 , wherein the step of setting different gear ratios of the two-roll mills comprises setting the gear ratios to different values ​​to generate backlash.

9. The method for producing an electrode for a secondary battery according to claim 6 , wherein the binder contains polytetrafluoroethylene (PTFE).

10. A secondary battery comprising the secondary battery electrode described in claim 2.

Citation Information

Patent Citations

  • JP1971018220Y1

  • The data sheet for the production of the seal - - - battery separator

    JP1973089339A

  • Dry electrode of energy storage device and manufacturing method thereof

    JP2019216101A

  • Compositions and methods for dry electrode films including microparticulate non-fibrillizable binders

    US20190305316A1

  • Electrically conductive, freestanding, porous, polymer film for use in capacitive deionization

    WO2005069927A2